Connection between oral health and chronic diseases - Di Fu; Xingyue Shu; Ge Zhou; Mengzhen Ji; Ga Liao; Ling Zou (MedComm)
Abstract Chronic diseases have emerged as a paramount global health burden, accounting for 74% of global mortality and causing substantial economic losses. The oral cavity serves as a critical indicator of overall health and is inextricably linked to chronic disorders. Neglecting oral health can exacerbate localized pathologies and accelerate the progression of chronic conditions, whereas effective management has the potential to reduce their incidence and mortality. Nevertheless, limited resources and lack of awareness often impede timely dental intervention, delaying optimal therapeutic measures. This review provides a comprehensive analysis of the impact of prevalent chronic diseases—such as diabetes mellitus, rheumatoid arthritis, cardiovascular disorders, and chronic respiratory diseases—on oral health, along with an exploration of how changes in oral health affect these chronic conditions through both deterioration and intervention mechanisms. Additionally, novel insights into the underlying pathophysiological mechanisms governing these relationships are presented. By synthesizing these advancements, this review aims to illuminate the complex interrelationship between oral health and chronic diseases while emphasizing the urgent need for greater collaboration between dental practitioners and general healthcare providers to improve overall health outcomes.